Understanding the structural and magnetic properties of Ni0.77Fe0.16Cu0.05Cr0.02 by mechanical alloying - Sim, Wenchao. (2009)
Nanomagnetic materials have been widely employed in the industry as they possess special magnetic properties. Nickel based soft magnetic materials which have low coercivity and high permeability have been used on recording heads, transformers and magnetic shielding materials. The aim of this final year project is to investigate the effects of mechanical alloying of Ni0.77Fe0.16Cu0.05Cr0.02 (mumetal) on its magnetic properties. The mumetal powders are synthesized by planetary high energy ball milling under argon atmosphere for milling ranging from 0 hr to 96 hr. Subsequently, investigation and evaluation on the crystallite size, composition and morphology by the use of X-ray diffraction (XRD) and scanning electron microscopy (SEM). The magnetic properties were examined by vibrating sample magnetometer (VSM). Results shown that with increasing milling time, the particle size decreases and after 12 hrs, crystallite size of 12nm mumetal was formed. The lattice parameter increases due to the binding of different elements of different lattice parameters. Saturation magnetization increases with milling time whereas the coercivity and retentivity have an opposite effect.